Newsletter from behind the Iron Curtain : reports on communist activities in Eastern Europe - Eesti Rahvusfond (Sweden); Estonian National Council (Stockholm, Sweden). Information Service in United States.; Latvian Information Service (Stockholm, Sweden); Latviešu nacionālais fonds. (Estonian Information Center, 1947)
"Reports on communist activities in Eastern Europe."With indexes.Current frequency: 52/year.